2019
DOI: 10.1111/apt.15241
|View full text |Cite
|
Sign up to set email alerts
|

Chronic continuous abdominal pain: evaluation of diagnostic features, iatrogenesis and drug treatments in a cohort of 103 patients

Abstract: Summary Background Chronic continuous abdominal pain (CCAP) is characteristic of centrally mediated gastrointestinal pain disorders. It consumes significant healthcare resources yet is poorly understood, with minimal cohort‐specific data in the literature. Aims To examine in a large cohort of CCAP patients, (a) diagnostic features, (b) iatrogenic impact of opioids and surgery, (c) drug treatment effects and tolerance. Methods Consecutive tertiary CCAP referrals to a neurogastroenterology clinic (2009‐2016) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 31 publications
2
15
0
12
Order By: Relevance
“…Indeed opioids can be detrimental in this setting due to their antimotility effects, worsen pain due opioid induced hyperalgesia, 30 and potentially increase infection risk, 31 which is particularly important when considering HPN 32 . The current survey data are thus in accordance with an increasing body of evidence 33 and recently published clinical guidelines to support use of centrally acting gut‐brain neuromodulators rather than the standard use of opioid medications to target this type of neuropathic pain 34,35 . Notably, respondents highlighted the importance of the multidisciplinary care including clinical psychology.…”
Section: Discussionsupporting
confidence: 79%
“…Indeed opioids can be detrimental in this setting due to their antimotility effects, worsen pain due opioid induced hyperalgesia, 30 and potentially increase infection risk, 31 which is particularly important when considering HPN 32 . The current survey data are thus in accordance with an increasing body of evidence 33 and recently published clinical guidelines to support use of centrally acting gut‐brain neuromodulators rather than the standard use of opioid medications to target this type of neuropathic pain 34,35 . Notably, respondents highlighted the importance of the multidisciplinary care including clinical psychology.…”
Section: Discussionsupporting
confidence: 79%
“…226 Evidence from a large cohort of patients with severe chronic continuous abdominal pain showed that combinations of neuropathic analgesics (eg, duloxetine plus gabapentin) were more efficacious than monotherapy. 287 Vigilance for the development of the serotonin syndrome for some combinations, especially those involving both SSRIs and SNRIs, is required. Symptoms include fever, hyperreflexia, tremor, sweating and diarrhoea.…”
Section: Guidelinesmentioning
confidence: 99%
“…For example, a study reported 81% allodynia was found in patients with chronic continuous abdominal pain (CCAP). 14 It can be further explained that if afferent pathways between allodynia and abdominal pain can converge in the posterior horn of the spinal cord or if they can enhance afferent signals, two types of pain will interact with each other. It means visceral pain can be presented as somatogenic pain, and vice versa.…”
Section: Discussionmentioning
confidence: 99%